Relationship between Neuropathic Pain and Obesity. (29th March 2016) - Hozumi, Jun; Sumitani, Masahiko; Matsubayashi, Yoshitaka; Abe, Hiroaki; Oshima, Yasushi; Chikuda, Hirotaka; Takeshita, Katsushi; Yamada, Yoshitsugu
Abstract : Objectives . Overweight negatively affects musculoskeletal health; hence obesity is considered a risk factor for osteoarthritis and chronic low back pain. This was conducted to determine if obesity affects neuropathic pain, usually considered unrelated to the weight-load on the musculoskeletal system. Methods . Using a cut-off body mass index value of 25, 44 patients with neuropathic pain were grouped into a "high-BMI" group and a "normal-BMI" group. Results . The numeric rating scale of the high-BMI group was significantly higher than that of the normal-weight group (P < 0.05 ). The total NPSI scores were significantly higher (P < 0.01 ), and the paroxysmal pain and the negative symptoms were more serious in the high-BMI group than in the normal-BMI group. The high-BMI subjects also had significantly higher SF-MPQ scores (P < 0.05 ). However, both physical and mental health status on the SF-36 were comparable between the groups. Discussion . Neuropathic pain that did not arise from musculoskeletal damage was higher in the high-BMI patients. Paroxysmal pain was more severe, suggesting that neural damage might be aggravated by obesity-associated inflammation. These findings should have needed to be confirmed in future studies.